Tyro3 promotes the maturation of glutamatergic synapses - Miao, Sheng; Fourgeaud, Lawrence; Burrola, Patrick G.; Stern, Shani; Zhang, Yuhan; Happonen, Kaisa E.; Novak, Sammy Weiser; Gage, Fred H.; Lemke, Greg (Frontiers in Neuroscience, 2024)
The receptor tyrosine kinase Tyro3 is abundantly expressed in neurons of the neocortex, hippocampus, and striatum, but its role in these cells is unknown. We found that neuronal expression of this receptor was markedly up-regulated in the postnatal mouse neocortex immediately prior to the final development of glutamatergic synapses. In the absence of Tyro3, cortical and hippocampal synapses never completed end-stage differentiation and remained electrophysiologically and ultrastructurally immature. Tyro3 -/-cortical neurons also exhibited diminished plasma membrane expression of the GluA2 subunits of AMPA-type glutamate receptors, which are essential to mature synaptic function. Correspondingly, GluA2 membrane insertion in wild-type neurons was stimulated by Gas6, a Tyro3 ligand widely expressed in the postnatal brain. Behaviorally, Tyro3 -/-mice displayed learning enhancements in spatial recognition and fear-conditioning assays. Together, these results demonstrate that Tyro3 promotes the functional maturation of glutamatergic synapses by driving plasma membrane translocation of GluA2 AMPA receptor subunits.